Analysis Numerical Discontinuity of Thin Walled Tube Subjected Low Velocity Impact - Rabeta, Bismil; Sitompul, Sahril Afandi (SENATIK STT Adisutjipto, 2018)
Accident of some countries that have high gross domestic product (GDP) significantly increasing[1]. This event cause fatal for passengers especially if there an accident on the front vehicle[3]. Therefore, the main aspects of car design are very important, one of them is  crash box. Crash boxes are designed to absorb impact energy due to collisions through progressive buckling. In the crushing box design, the tube can be given continuity in the form of a circular hole that has been carried out by previous researchers which provides a deceleration at the safety level on passenger body. In this study a numerical analysis conducted using tube with ellipse discontinuity by varying the ratio of ellipse hole in the crushing box to D/b ratio 0.0, 0.2, 0.3, 0.5. The results of this study found that the tube with D/b 0.0 has the highest peak  force than the other ratio.